2017
DOI: 10.3389/fevo.2017.00046
|View full text |Cite
|
Sign up to set email alerts
|

Two Neural Measures Differ between Urban and Rural Song Sparrows after Conspecific Song Playback

Abstract: Urbanization is a critical form of environmental change that can affect the physiology and behavior of wild animals and, notably, birds. One behavioral difference between birds living in urban and rural habitats is that urban males show elevated boldness or territorial aggression in response to simulated social challenge. This pattern has been described in several populations of song sparrow, Melospiza melodia. Such behavioral differences must be underpinned by differences in the brain, yet little work has exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…Alternatively, we may have seen differences in IEG activation in response to predator and conspecific playbacks if had we examined expression of a different IEG, for example, c-Fos. Several studies have found differences in the expression of different IEGs in response to the same stimulus (Sewall and Davies, 2017;Kimball et al, 2022). We chose ZENK because it is commonly used to assess neuronal activity in songbirds in response to acoustic stimuli (Maney et al, 2003;Rivera et al, 2019); however, future studies should consider using multiple IEGs to examine the brain's response to positive, neutral, or aversive auditory cues.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, we may have seen differences in IEG activation in response to predator and conspecific playbacks if had we examined expression of a different IEG, for example, c-Fos. Several studies have found differences in the expression of different IEGs in response to the same stimulus (Sewall and Davies, 2017;Kimball et al, 2022). We chose ZENK because it is commonly used to assess neuronal activity in songbirds in response to acoustic stimuli (Maney et al, 2003;Rivera et al, 2019); however, future studies should consider using multiple IEGs to examine the brain's response to positive, neutral, or aversive auditory cues.…”
Section: Discussionmentioning
confidence: 99%
“…We carried out immunohistochemistry for ZENK in every third section from both hemispheres following established protocols for application in bird tissue (Sockman et al, ; Sewall and Davies, ). Briefly, we blocked the tissue in 1% hydrogen peroxide followed by 2% normal goat serum and an Aviden Biotin blocking kit (Vector Labs, SP‐2001, Burlingame, CA) before incubating in Egr‐1 primary antibody (raised in rabbit, Santa Cruz Biotechnology, SC‐189, Dallas, TX) at a ratio of 1–8,000 for 48 h at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…We located the social behavior network regions following Maney et al (2008) and references therein (see also Sewall and Davies, 2017). Specifically, to identify BSTm, we followed Aste et al (1998) and Maney et al (2008) and placed a 0.2-mm 2 counting circle dorsal to the anterior commissure in two tissue sections.…”
Section: Female Song Re-exposure and Immunohistochemistrymentioning
confidence: 99%